Polish Seminar on Acoustics (OSA 2000) - Archives of Acoustics, Editorial Board (Archives of Acoustics, 2000)
XLVII OSA’2000 is a significant scientific forum for presenting the experience and achievements from basic fields of both the experimental and theoretical acoustics as wellas its applications. The seminar is an overview of the recent, mainly Polish, contributions to the developmentof research in the field. It is also an opportunity for public discussion and exchange of scientific views concerning such an important interdisciplinary science as acoustics. Last but not least, it plays a crucial role in integrating the scientists.The papers presented at XLVII OSA’2000 have been divided into plenary papers and papers concerning different areas of acoustics.